METODE DAKWAH (STUDI AL-QUR’AN SURAH AN-NAHL AYAT 125) - Nurhidayat Muh Said (Fakultas Dakwah dan Komunikasi, 2015)
This paper discusses methods of propaganda Qur'anic perspectives. In Surat an-Nahl verse 125 mentioned three methods of propaganda that is bilhikmah, walmauidzah al-Hasanah, wa hiya jadilhum billaty ahsan. The division is directed to a method of object mapping propaganda that can be categorized into three major groups of intellectuals, ordinary people and the people are against the teachings of Islam. ). If preaching to the laity (beginner), do not ever force, do not convey the problems can not be understood or considered difficult by them. Because in accordance temperament, nafs will flee if objections and will oppose and antagonize goodness then search (justification) for his actions.